2009
DOI: 10.1073/pnas.0809063106
|View full text |Cite
|
Sign up to set email alerts
|

Filter feeders and plankton increase particle encounter rates through flow regime control

Abstract: Collisions between particles or between particles and other objects are fundamental to many processes that we take for granted. They drive the functioning of aquatic ecosystems, the onset of rain and snow precipitation, and the manufacture of pharmaceuticals, powders and crystals. Here, I show that the traditional assumption that viscosity dominates these situations leads to consistent and largescale underestimation of encounter rates between particles and of deposition rates on surfaces. Numerical simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 42 publications
2
84
0
Order By: Relevance
“…That is, a true sieving process in which all particles will be retained if greater than some minimal diameter determined by aerosol filtration theory, which takes into account particle size relative to the diameter and spacing of cylindrical wires in the mesh. In most cases, scales of relative velocity and physical length are small enough to ensure creeping flow at Reynolds number (Re) << 1, but there are cases of Re > 1 for which Humphries (2009) has shown that encounter rates of particles increase significantly above those predicted by traditional aerosol theory based on creeping (laminar) flow.…”
Section: Details Of the Capture Processmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, a true sieving process in which all particles will be retained if greater than some minimal diameter determined by aerosol filtration theory, which takes into account particle size relative to the diameter and spacing of cylindrical wires in the mesh. In most cases, scales of relative velocity and physical length are small enough to ensure creeping flow at Reynolds number (Re) << 1, but there are cases of Re > 1 for which Humphries (2009) has shown that encounter rates of particles increase significantly above those predicted by traditional aerosol theory based on creeping (laminar) flow.…”
Section: Details Of the Capture Processmentioning
confidence: 99%
“…of the porous structure and shows to what extent particles less than the pore-size may intercept the elements, all depending on geometry, particle size and Reynolds number. Here the case of the intermediate Reynolds number range (0.1 to 50) has been studied by Palmer et al (2004) and more recently by Humphries (2009). The fraction of particles that stick when making contact is called the 'striking coefficient' (Jumars 1993).…”
Section: Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…EVR for C. sowerbyi assumes that the dominant prey encounter mechanism is direct interception and relies upon Re ranging from 0.2-2 around the tentacles. We can estimate the EVR using intermediate Re estimates (Humphries, 2009) …”
Section: Flow and Prey Encountermentioning
confidence: 99%
“…For example, at high Reynolds number (Re), diffusive deposition is negligible, while the compression of streamlines around the feeding structure provides a potential mechanism for increased encounter of particles. 5 At low Re, inertia is negligible and the feeding structure has to manipulate the surrounding fluid to generate feeding currents that bring suspended particles closer to the feeding organ.…”
Section: Introductionmentioning
confidence: 99%